(untitled) (Conferencea, 2024)
Improving the efficiency of the insurance services market in Uzbekistan is one of the most important sectors in improving the country’s macroeconomic stability and economic potential At the meeting of the President of the Republic of Uzbekistan on July 10, 2019, dedicated to the "Discussion of the Insurance Market Development Issues", he said that "not a controller, but introducing advanced and modern standards to the industry, creating a truly competitive environment among all participants, insurance it was emphasized that a structure that develops the market is needed.